MAXILLARY SINUS FLOOR ELEVATION PROCEDURE, A NARRATIVE REVIEW OF SINUS ANATOMY AND DIFFERENT ELEVATION APPROACHES - Mustafa M. Tashkandi (Romanian Journal of Oral Rehabilitation)
Aim: The aim of this study is to review different maxillary sinus elevation technique and its relevant to the surrounding structure. Material and Methods: A comprehensive literature search was conducted in PubMed, Scopus, Web of Science, and the Cochrane Library using keywords related to sinus augmentation and dental implants. Studies published in the last 20 years were included to ensure relevance and up-to-date findings. Result: Implant placement in the posterior maxilla has changed due to sinus elevation techniques; the approach chosen depends on patient-specific characteristics, bone quality, and residual bone height (RBH). When the maxilla is significantly atrophic (RBH < 4 mm), the lateral window approach is the best option because it provides great access but has a higher risk of complications. While balloon-assisted sinus lift , Versha burs and piezoelectric surgery offer less invasive and more accurate options, the trans-crestal method is best suited for moderate RBH 5mm < and has lower morbidity. While sequential treatments are advised for lower RBH, simultaneous implant insertion works well for adequate RBH (>5 mm) and primary stability. Minimizing problems and attaining long-term success need careful patient selection and adherence to technique-specific procedures. Conclusion: With the development and improvement of sinus elevation procedures, clinicians now have more alternatives to maximize therapy results. To reduce difficulties and guarantee long-term success in implant rehabilitation, a comprehensive preoperative evaluation, customized treatment planning, and adherence to technique-specific guidelines are essential.